Keanekaragaman Lumut (Bryphyta) Di Kawasan Danau Tambing Taman Nasional Lore Lindu Dan Pengembangannya Sebagai Media Pembelajaran - Barnabas, Sri Marthati (Mitra Sains, 2016)
This research was taken place around Tambing Lake, National Park Lore Lindu, Sigi Regency in Central Sulawesi Province. This area encompassed tourism destination and it couid be found a lot of Bryophyta that was adopted to be a learning resources.This research aimed to identifying identify diversity and to develop a learning media by using image cards from every spesies identified. This research employed method obstruction. Developing learning media was based on the 4-D development model by Thiagarajan. Sample was collected from 8 obstruction. the sample was stated by using free collection technique of is obstruction. The data were analyzed descriptively and identified by using the key of determination and image and books that had been patented: than the developing image were used cars as the developing instructional media. It was found 19 species of Bryophyte, dealing with 7 species of Hepaticopsida class and 12 species of Bryopsida class. Furthermore, in relation to the result of development of image cards. It was obtained the average percentage from the reviewer of media, content, and design, 94%, from the peer teacher assesment, 90%, from the small group student assesment, 87% and from the large group students assesment, 88%. The four average of the result were 90%. It could be converted into a good categori.